Inflammatory mediators: Parallels between cancer biology and stem cell therapy - A Patel; Andrew C Heinrich; Bobby Y Reddy; Pranela Rameshwar (Dove Medical Press, 2009)
Shyam A Patel1,2,3, Andrew C Heinrich2,3, Bobby Y Reddy2, Pranela Rameshwar21Graduate School of Biomedical Sciences, University of Medicine and Dentistry of New Jersey, Newark, NJ, USA; 2Department of Medicine – Division of Hematology/Oncology, New Jersey Medical School, University of Medicine and Dentistry of New Jersey, Newark, NJ, USA; 3These authors contributed equally to this workAbstract: Inflammation encompasses diverse molecular pathways, and it is intertwined with a wide array of biological processes. Recently, there has been an upsurge of interest in the interactions between mediators of inflammation and other cells such as stem cells and cancer cells. Since tissue injuries are associated with the release of inflammatory mediators, it would be difficult to address this subject without considering the implications of their systemic effects. In this review, we discuss the effects of inflammatory reactions on stem cells and extrapolate on information pertaining to cancer biology. The discussion focuses on integrins and cytokines, and identifies the transcription factor, nuclear factor-kappa B (NFκB) as central to the inflammatory response. Since stem cell therapy has been proposed for type II diabetes mellitus, metabolic syndrome, pulmonary edema, these disorders are used as examples to discuss the roles of inflammatory mediators. We propose prospects for future research on targeting the NFκB signaling pathway. Finally, we explore the bridge between inflammation and stem cells, including neural stem cells and adult stem cells from the bone marrow. The implications of mesenchymal stem cells in regenerative medicine as pertaining to inflammation are vast based on their anti-inflammatory and immunosuppressive effects. Such features of stem cells offer great potential for therapy in graft-versus-host disease, conditions with a significant inflammatory component, and tissue regeneration.Keywords: mesenchymal stem cells, cancer, cytokines, NF kappa B